Preparation method of Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity
The preparation of Fe-doped cobalt sulfide/nickel sulfide oxygen evolution catalyst by one-step hydrothermal method solved the problem of insufficient charge transfer capability of NiCo bimetallic sulfide catalyst, and achieved efficient and stable catalytic performance in different electrolytes.
Patent Information
- Application Number
- CN202411952944.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing NiCo bimetallic sulfide catalysts are limited by the charge transfer ability, which makes it difficult to fully demonstrate their intrinsic catalytic properties.
Fe-doped cobalt sulfide/nickel sulfide oxygen evolution catalyst was prepared by one-step hydrothermal method. Fe-Co4S3/Ni3S2/NF nanomaterials were prepared by dissolving thiourea, NH4F, cobalt acetate and ferric nitrate nohydrate in a mixed solution of deionized water and ethylene glycol, and hydrothermal reaction was carried out at 130°C to 150°C.
The catalyst exhibits high catalytic activity in pure water of 1M KOH, simulated seawater and electrolyte in natural seawater, has a low overpotential and is stable, and can be stably catalyzed in natural seawater for at least 100 hours.
Smart Images

Figure CN119710808A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrocatalytic water splitting. Background Art
[0002] In the long-term industrialization process, with the rapid growth of the global population and the rapid development of the world economy, human demand for energy is increasing day by day. In the existing energy structure, traditional fossil fuels (coal, oil, natural gas, etc.) are still the main source of energy consumption in today's society. However, it should be noted that fossil fuels are non-renewable energy sources with limited reserves. Due to the high energy density and clean properties of hydrogen, it has become a promising alternative energy source for fossil fuels. Electrocatalytic decomposition of water to produce hydrogen has become a major research hotspot for electrochemical energy storage and conversion, but practical challenges still exist. The anodic oxygen evolution reaction (OER) has a relatively high thermodynamic (237 kJ mol -1 ), which leads to overpotential and energy loss in the water splitting process, and is the bottleneck for realizing the industrialization of water splitting electrolyzers. In order to promote the electrolysis of water, it is necessary to find electrocatalysts with high activity and high stability. Ir- / Ru-oxides are known highly active OER catalysts. However, their scarcity and high cost prevent these materials from being widely used. Therefore, it is of utmost importance to develop efficient, low-cost, precious metal-free materials as alternatives.
[0003] Sulfides of earth-abundant transition metals (Fe, Co, Ni, Mn, and W) with appropriate chemical compositions and reasonable morphologies have been developed as efficient water splitting electrocatalysts for OER. Compared with single transition metal sulfides, NiCo bimetallic sulfides exhibit excellent catalytic performance in OER. The catalytic performance of nickel-cobalt sulfide catalysts comes from the good conductivity of sulfides and the interaction between different transition metals, which leads to changes in electron distribution and thus enhances the intrinsic activity of the catalytic sites. Although some research progress has been made on NiCo bimetallic sulfide, the catalyst is limited by its charge transfer ability, and its intrinsic catalytic performance is difficult to fully exhibit. Summary of the invention
[0004] The present invention aims to solve the problem that the intrinsic catalytic performance of existing NiCo bimetallic sulfides is difficult to fully demonstrate due to the limitation of charge transfer ability, and further provides a method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity.
[0005] A method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity is carried out according to the following steps:
[0006] 1. Preparation of precursor solution:
[0007] Thiourea, NH4F, cobalt acetate and ferric nitrate nonahydrate were dissolved in a mixed solution of deionized water and ethylene glycol and stirred to obtain a clear light blue solution;
[0008] 2. Hydrothermal reaction:
[0009] The pretreated nickel foam is immersed in a clear light blue solution, heated to react at a temperature of 130° C. to 150° C., then naturally cooled to room temperature, and finally washed and dried, thereby completing the preparation method of the Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity.
[0010] The beneficial effects of the present invention are:
[0011] The present invention adopts a one-step hydrothermal method to prepare Fe-Co4S3 / Ni3S2 / NF nanomaterials. Nanosheets are densely grown on the surface of NF, which solves the problem that the existing NiCo bimetallic sulfide is limited by the charge transfer ability and its intrinsic catalytic performance is difficult to fully demonstrate. The preparation is simple and easy to synthesize.
[0012] The Fe-Co4S3 / Ni3S2 / NF nanomaterial prepared by the present invention is a working electrode, which has high catalytic activity in 1M KOH pure water, 1M KOH simulated seawater and 1M KOH natural seawater electrolytes: in 1M KOH pure water, at 50mA / cm 2 and 100mA / cm 2 In the simulated seawater of 1M KOH, at 50mA / cm 2 and 100mA / cm 2 In natural seawater with 1M KOH, at 50mA / cm 2 and 100mA / cm 2 The overpotentials required were 292 mV and 361 mV respectively; and it had stable catalytic activity in 1 M KOH natural seawater and could stably catalyze for at least 100 h.
[0013] The invention is used for a method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the SEM image of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1, a is a scale of 5 μm, b is a scale of 10 μm;
[0015] Figure 2 The XRD pattern of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1;
[0016] Figure 3 LSV of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1 in 1M KOH pure water, 1M KOH simulated seawater and 1M KOH natural seawater;
[0017] Figure 4 The Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1 and the catalyst electrode reported in the literature are 2 Overpotential comparison diagram of ;
[0018] Figure 5 At 100mA / cm 2 Below is the chronopotentiometry curve of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1 in 1M KOH natural seawater. DETAILED DESCRIPTION
[0019] Specific implementation method 1: This implementation method is a method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity, which is carried out according to the following steps:
[0020] 1. Preparation of precursor solution:
[0021] Thiourea, NH4F, cobalt acetate and ferric nitrate nonahydrate were dissolved in a mixed solution of deionized water and ethylene glycol and stirred to obtain a clear light blue solution;
[0022] 2. Hydrothermal reaction:
[0023] The pretreated nickel foam is immersed in a clear light blue solution, heated to react at a temperature of 130° C. to 150° C., then naturally cooled to room temperature, and finally washed and dried, thereby completing the preparation method of the Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity.
[0024] The beneficial effects of this embodiment are:
[0025] This embodiment adopts a one-step hydrothermal method to prepare Fe-Co4S3 / Ni3S2 / NF nanomaterials. Nanosheets are densely grown on the surface of NF, which solves the problem that the existing NiCo bimetallic sulfide is limited by the charge transfer ability and its intrinsic catalytic performance is difficult to fully demonstrate. The preparation is simple and easy to synthesize.
[0026] The Fe-Co4S3 / Ni3S2 / NF nanomaterial prepared in this embodiment is a working electrode and has high catalytic activity in 1M KOH pure water, 1M KOH simulated seawater and 1M KOH natural seawater electrolytes: in 1M KOH pure water, at 50mA / cm 2 and 100mA / cm 2In the simulated seawater of 1M KOH, at 50mA / cm 2 and 100mA / cm 2 In natural seawater with 1M KOH, at 50mA / cm 2 and 100mA / cm 2 The overpotentials required were 292 mV and 361 mV respectively; and it had stable catalytic activity in 1 M KOH natural seawater and could stably catalyze for at least 100 h.
[0027] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the mass ratio of thiourea to NH4F in step 1 is 1:(0.05-0.13). Others are the same as specific embodiment 1.
[0028] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the mass ratio of thiourea to cobalt acetate in step 1 is 1:(0.17-0.33). Others are the same as specific embodiment 1 or 2.
[0029] Specific embodiment 4: This embodiment is different from Specific embodiments 1 to 3 in that the mass ratio of thiourea to ferric nitrate nonahydrate in step 1 is 1:(0.06-0.22). Others are the same as Specific embodiments 1 to 3.
[0030] Specific embodiment 5: This embodiment differs from Specific embodiments 1 to 4 in that the volume ratio of the mass of thiourea described in step 1 to the mixed solution of deionized water and ethylene glycol is 1 mg: (0.1-0.2) mL. The rest is the same as Specific embodiments 1 to 4.
[0031] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the volume ratio of deionized water to ethylene glycol in the mixed solution of deionized water and ethylene glycol described in step 1 is 1:(1.5-2.5). Other aspects are the same as specific implementation examples 1 to 5.
[0032] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the pre-treated nickel foam described in step 2 is specifically prepared according to the following steps: washing the nickel foam with ethanol, 0.1 mol / L to 3.0 mol / L HCl solution and water to remove the oxide layer, then vacuum drying for 4h to 12h at a temperature of 40°C to 100°C, and finally sealing the vacuum packaging bag for standby use; the porosity of the nickel foam is 96% to 98%, and the specific gravity is 0.2 to 0.3. Others are the same as specific embodiments 1 to 6.
[0033] Specific embodiment 8: This embodiment differs from Specific embodiments 1 to 7 in that: in step 2, the heating reaction is carried out at a temperature of 130° C. to 160° C. for 6 h to 10 h. The rest is the same as Specific embodiments 1 to 7.
[0034] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 2, the temperature is raised to 130° C. to 160° C. at a heating rate of 1° C. / s to 2° C. / s. The rest is the same as specific embodiments 1 to 8.
[0035] Specific embodiment 10: This embodiment differs from Specific embodiments 1 to 9 in that the cleaning and drying described in step 2 is to rinse with deionized water and ethanol several times respectively, and then vacuum dry for 6h to 12h at a temperature of 60°C to 100°C. Others are the same as Specific embodiments 1 to 9.
[0036] The following examples are used to verify the beneficial effects of the present invention:
[0037] Embodiment 1:
[0038] A method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity is carried out according to the following steps:
[0039] 1. Preparation of precursor solution:
[0040] 150 mg of thiourea, 10 mg of NH4F, 30 mg of cobalt acetate and 20 mg of ferric nitrate nonahydrate were dissolved in a mixed solution of deionized water and ethylene glycol and stirred to obtain a clear light blue solution;
[0041] 2. Hydrothermal reaction:
[0042] The pretreated nickel foam was immersed in a clear light blue solution and transferred to a 50 mL Teflon-lined stainless steel autoclave. The temperature was raised to 140°C at a heating rate of 1.5°C / s. The reaction was heated at 140°C for 7 h, then naturally cooled to room temperature, and finally washed and dried to obtain a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity, named Fe-Co4S3 / Ni3S2 / NF electrode.
[0043] The mixed solution of deionized water and ethylene glycol is prepared by mixing 7 mL of deionized water with 14 mL of ethylene glycol.
[0044] The pretreated nickel foam described in step 2 is specifically prepared according to the following steps: the nickel foam is washed with ethanol, 3 mol / L HCl solution and water respectively to remove the oxide layer, then vacuum dried for 12 hours at a temperature of 60°C, and finally sealed in a vacuum packaging bag for standby use; the porosity of the nickel foam is 96% to 98%, and the specific gravity is 0.2 to 0.3.
[0045] The cleaning and drying in step 2 specifically involves rinsing with deionized water and ethanol for several times, and then vacuum drying at 60° C. for 12 hours.
[0046] Figure 1 This is the SEM image of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1. The scale of a is 5μm, and the scale of b is 10μm. The morphology of the catalyst was analyzed using SEM technology. It can be seen from the figure that the electrode is composed of nanosheets densely grown on the surface of NF.
[0047] Figure 2 This is the XRD pattern of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1; it can be seen from the figure that the diffraction peaks of the Fe-Co4S3 / Ni3S2 / NF electrode at 29.9°, 31.1°, 36.2°, 51.9°, 61.7°, 64.9°, 73.0° and 76.8° are respectively attributed to the (311), (222), (400), (440), (622), (444), (731), (732) and (733)(800) crystal planes of Co4S3 (PDF#00-002-1338). The diffraction peaks at 21.8°, 31.1°, 37.8°, 44.4°, 49.8°, 55.2° and 73.1° correspond to the (101), (110), (003), (202), (113), (122) and (214) crystal planes of Ni3S2 (PDF#01-079-8914), respectively. Therefore, the Fe-Co4S3 / Ni3S2 / NF electrode is composed of two phases, Co4S3 and Ni3S2.
[0048] The test was carried out using a three-electrode system, with the Fe-Co4S3 / Ni3S2 / NF electrode as the working electrode, the Hg / HgO electrode as the reference electrode, and the graphite electrode as the counter electrode; the test results are shown in Figures 3 to 5 .
[0049] Figure 3 LSV of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1 in 1M KOH pure water, 1M KOH simulated seawater and 1M KOH natural seawater; As can be seen from the figure, in 1M KOH pure water, at 50mA / cm 2 and 100mA / cm2 Under the condition of 1M NaCl, the Fe-Co4S3 / Ni3S2 / NF electrode requires an overpotential of 286mV and 329mV respectively; in the simulated seawater (0.5M NaCl) of 1M KOH, at 50mA / cm 2 and 100mA / cm 2 Under the condition of 1M KOH, the Fe-Co4S3 / Ni3S2 / NF electrodes require overpotentials of 296mV and 344mV respectively; in natural seawater with 1M KOH, at 50mA / cm 2 and 100mA / cm 2 Under the same conditions, the Fe-Co4S3 / Ni3S2 / NF electrodes required overpotentials of 292 mV and 361 mV, respectively.
[0050] Figure 4 The Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1 and the catalyst electrode reported in the literature are 2 Overpotential comparison diagram; it can be seen from the figure that in 1M KOH natural seawater, the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1 is still superior to the catalyst electrode reported in the literature.
[0051] Figure 4 The data of S-NiFeSe2 refer to XWChen, YHY u1, XQHan, H.Wang, YJ Hua, DXWu, PLDeng, JXXiao, XLTian and J.Li, Sci.China chem., 2024, 67, 2747-2754.
[0052] Figure 4 The data of Co-Ni3S2 / NF refer to M.Yue, X.He, SJSun, YT Sun, MSHamdy, M.Benaissa, AAM Salih, J.Liu, NanoResearch, 2024, 17, 1050-1055.
[0053] Figure 4 The data of Fe-Co-S / Cu2O / Cu in the paper refer to J.Sun, P.Song, H.Zhou, L.Lang, X.Shen, Y.Liu, X.Cheng, X.Fu, G.Zhu.Appl.Surf.Sci,2021,567,150757-150768.
[0054] Figure 4The data of Co2(OH)3Cl in the article refer to L.Zhuang, J.Li, K.Wang, Z.Li, M.Zhu, Z.Xu, Adv.Funct.Mater, 2022, 32, 2201127.
[0055] Figure 4 The data of Ni(OH)2-TCNQ / GP refer to LC Zhang, JQ Wang, PY Liu, J. Liang, YS Luo, GW Cui, B. Tang, Q. Liu, XD Yan, HG Hao, ML Liu, R. Gao and XP Sun, Nano Res., 2022, 15, 6084-6090.
[0056] Figure 4 MediumFeO x -Ni2S3 / NF data reference WJHao, JL Fan, X.Xu, YRZhang, H.Yang, SG Weng, SW Deng, S.Weng, YH Guo, Dalton Trans. 2021, 50, 13312-13319.
[0057] Figure 4 For the data of NiCoP / NiCo-LDH, please refer to Y.Wu, Z.Tian, S.Yuan, Z.Qi, Y.Feng, Y.Wang, R.Huang, Y.Zhao, J.Sun, W.Zhao, W.Guo, J.Feng, J.Sun.Chem.Eng.J, 2021, 411, 128538.
[0058] Figure 5 At 100mA / cm 2 The chronopotentiometry curve of the Fe-Co4S3 / Ni3S2 / NF electrode prepared in Example 1 in 1M KOH natural seawater is shown below. As can be seen from the figure, the Fe-Co4S3 / Ni3S2 / NF electrode can stably catalyze for at least 100 hours, and there is no obvious voltage increase during this process. This shows that the material has stable catalytic activity in alkaline natural seawater.
Claims
1. A method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity, characterized in that It is carried out in the following steps:
1. Preparation of precursor solution: Thiourea, NH4F, cobalt acetate and ferric nitrate nonahydrate were dissolved in a mixed solution of deionized water and ethylene glycol and stirred to obtain a clear light blue solution; 2. Hydrothermal reaction: The pretreated nickel foam is immersed in a clear light blue solution, heated to react at a temperature of 130° C. to 150° C., then naturally cooled to room temperature, and finally washed and dried, thereby completing the preparation method of the Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity.
2. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that The mass ratio of thiourea to NH4F described in step 1 is 1:(0.05-0.13).
3. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that The mass ratio of thiourea to cobalt acetate described in step 1 is 1:(0.17-0.33).
4. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that The mass ratio of thiourea to ferric nitrate nonahydrate described in step 1 is 1:(0.06-0.22).
5. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that The volume ratio of the mass of thiourea described in step 1 to the mixed solution of deionized water and ethylene glycol is 1 mg: (0.1-0.2) mL.
6. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that The volume ratio of deionized water to ethylene glycol in the mixed solution of deionized water and ethylene glycol described in step 1 is 1:(1.5-2.5).
7. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that The pretreated nickel foam described in step 2 is specifically prepared according to the following steps: the nickel foam is cleaned with ethanol, 0.1 mol / L to 3.0 mol / L HCl solution and water to remove the oxide layer, and then vacuum dried for 4h to 12h at a temperature of 40°C to 100°C, and finally sealed in a vacuum packaging bag for standby use; the porosity of the nickel foam is 96% to 98%, and the specific gravity is 0.2 to 0.
3.
8. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that In step 2, the reaction is heated at a temperature of 130° C. to 160° C. for 6 h to 10 h.
9. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that In step 2, the temperature is raised to 130°C to 160°C at a heating rate of 1°C / s to 2°C / s.
10. The method for preparing a Fe-doped cobalt sulfide / nickel sulfide oxygen evolution catalyst with high catalytic activity according to claim 1, characterized in that The cleaning and drying in step 2 specifically involves rinsing with deionized water and ethanol for several times, and then vacuum drying at a temperature of 60° C. to 100° C. for 6 h to 12 h.